A nationwide cohort study of slipped capital femoral epiphysis. Issue 12 (29th June 2017) - Perry, Daniel C; Metcalfe, David; Costa, Matthew L; Van Staa, Tjeerd
Abstract : Objectives: To describe the epidemiology of slipped capital femoral epiphysis (SCFE), to examine associations with childhood obesity and socioeconomic deprivation, and to explore factors associated with diagnostic delays. Design: Historic cohort study using linked primary and secondary care data from the Clinical Practice Research Datalink and Hospital Episode Statistics. Setting: All contacts with healthcare services, including emergency presentations, outpatient appointments, inpatient admissions and primary care visits, within the UK National Health Service. Patients: All individuals <16 years old with a diagnosis of SCFE and whose electronic medical record was held by one of 650 primary care practices in the UK between 1990 and 2013. Main outcome measures: Annual incidence, missed opportunities for diagnosis and diagnostic delay. Results: Over the 23-year period the incidence remained constant at 4.8 (95% CI 4.4 to 5.2) cases per 100, 000 0–16-year-olds. There was a strong association with socioeconomic deprivation. Predisease obesity was also strongly associated with SCFE; mean predisease z-score of body mass index was 1.43 (95% CI 1.20 to 1.68) compared with the UK reference mean. Diagnostic delays were common, with most children (75.4%) having multiple primary care contacts with relevant symptomatology, and those who presented with knee pain having significantly longer diagnostic delay (median 161 (IQR 27–278) days) than those with hip pain (20 (5–126)) or gait abnormalities (21 (7–72)). Conclusions: SCFE has a strong association with both area-level socioeconomic deprivation and predisease obesity. The majority of patients with SCFE are initially misdiagnosed and those presenting with knee pain are particularly at risk.